INDONESIAN ECONOMIC OUTLOOK 2015!, SUATU KAJIAN KRITIS - Djaka Suryadi (Jurnal Asy-Syukriyyah, 2014)
After going through the process of transition from the era of SBY's administration, the new government that is exhausting, then with the more mature democracy in Indonesia, the Indonesian president's leadership succession to - 7 could take place, namely the election of Ir Djoko Widodo as President, and Drs Jusuf Kalla as Vice President, something very interesting from kepempinan President to - 7 and his staff, because it is dominated by businessmen with a good track record, who have passed through the track record of the Commission and its financial transactions INTRAC, be grateful and Indonesia in the future certainly can follow his associates namely Singapore, which in a few decades has been transformed into the Developed Countries in Southeast Asia, with a per capita income of nearly US $ 50,000, Of course it is proper leadership is still in transition and be of the full support of the Legislature, Judiciary and the wider community, for the success of the entire program - a program established by the government through the state budget funds, the budget and the private sector, whose composition has led to the development and improvement of facilities digenjotnya massive infrastructure in the sector - the productive sectors, creating a conducive investment climate comfort while maintaining the stability of Indonesia is a country that is safe and conducive to investment The current government strategy is to manage the State is like managing the company, which makes the system across all lines and integrated by information technology systems, good infrastructure for efficient and maximum connectivity, socialization healthy lifestyle, with the performance of productive work for the whole community productive age, of the future of this country will become a developed country that is respected by other countries Implementation of state funds will be able to run with the maximum results for the participation of all stakeholders and all components of Indonesian society united support and success, the entire program - a program of government, in the form of high performance and productivity, so that development can work well, and that Equally important is the broad role of the construction supervision system supported by awareness together would improve the results of the monitoring system, and make the findings for improvement - continuous improvement, together - together in carrying out their roles – eachThe author presents a critical review of this try to make it more appealing to the method of SWOT analysis approach!